2017
DOI: 10.5152/turkjorthod.2016.0015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Blood Spot Dehydroepiandrosterone Sulfate Levels in Adjunct to Hand Wrist Radiographs as Skeletal Maturity Indicator

Abstract: Objective: The purpose of this study was to find out whether blood spot Dehydroepiandrosterone Sulfate (DHEAs) levels can be used as Skeletal Maturity Indicators (SMI) by correlating them to hand-wrist maturation stages. Methods:The cross sectional study population consisted of 107 subjects (62 females and 45 males) 5-25 years old. Hand-wrist radiographs were obtained, and the subjects were divided into 5 groups based on the hand-wrist skeletal maturity stages. A blood spot sample was collected and immunoassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 30 publications
(21 reference statements)
0
12
1
Order By: Relevance
“…Two studies- Anusuya et al (2020) and Srinivasan and Premkumar (2012)-assessed the levels of DHEA or DHEA-S and reported the association of highest biomarker levels during SMI 4-5 and CS 4 staging, respectively. This was in stark contrast to the study by Venkatagiriappa et al (2016), who found that DHEA-S levels progressively increased from prepubertal to postpubertal HW stages and were independent of the growth status of the individual. Anusuya et al (2020) reported an earlier peak in female patients compared to Srinivasan and Premkumar (2012), who observed no differences between the sexes.…”
Section: Characteristics Of the Study Outcomescontrasting
confidence: 99%
See 4 more Smart Citations
“…Two studies- Anusuya et al (2020) and Srinivasan and Premkumar (2012)-assessed the levels of DHEA or DHEA-S and reported the association of highest biomarker levels during SMI 4-5 and CS 4 staging, respectively. This was in stark contrast to the study by Venkatagiriappa et al (2016), who found that DHEA-S levels progressively increased from prepubertal to postpubertal HW stages and were independent of the growth status of the individual. Anusuya et al (2020) reported an earlier peak in female patients compared to Srinivasan and Premkumar (2012), who observed no differences between the sexes.…”
Section: Characteristics Of the Study Outcomescontrasting
confidence: 99%
“…Among the studies with a cross-sectional study design, four (Masoud, 2008; Sinha et al, 2014; Srinivasan and Premkumar, 2012; Venkatagiriappa et al, 2016) utilised HW radiographs exclusively as radiographic SMI. Studies by Masoud (2008) and Venkatagiriappa et al (2016) divided the study participants into five groups according to the Fishman Staging (Fishman, 1982).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations